Regional Capital No More. How the Reform of the Territorial Government has Marginalized Polish Middle-sized Cities - Borys Cieślak; Paula Nagler; Frank van Oort (Tinbergen Institute, 2023)
Among Polish cities facing socio-economic difficulties are the former regional capitals which lost their administrative status due to the 1998 reform, reducing the number of regions from 49 to 16. Making use of this quasiexperimental setting, we assess the impact of the loss of administrative status on the affected cities with difference-in-differences models. Our findings show a significant negative impact on economic and, partly, on other dimensions of development. Restructuring and scaling of devolved regions resulted in 'leaving places behind'. The problematic socioeconomic trajectories of Poland's former regional capitals caused or accentuated by the reform suggest a sustained marginalization.
Keywords: R11; R15; R58; 330; Socioeconomic development; marginalization; decentralization; regional capital status